Regional public research, higher education, and innovative start-ups: An empirical investigation - Ronney Aamoucke; Michael Fritsch (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Based on detailed information about the regional knowledge base, particularly about universities, we find that regional public research and education have a strong positive impact on new business formation in innovative industries but not in industries classified as non-innovative. Measures for the presence and size of public academic institutions have more of an effect on the formation of innovative new businesses than indicators that reflect the quality of these institutions. We find relatively weak evidence for interregional spillovers of these effects. Our results clearly demonstrate the importance of localized knowledge and, especially, of public research for the emergence of innovative new businesses.
Keywords: L26; L60; L80; O18; R12; R30; 330; innovative start-ups; new business formation; regional knowledge; universities